Comparison of classical and modern methods for measuring and correcting for acquiescence. (29th April 2019) - Primi, Ricardo; Santos, Daniel; De Fruyt, Filip; John, Oliver P.
Abstract : Likert‐type self‐report scales are frequently used in large‐scale educational assessment of social‐emotional skills. Self‐report scales rely on the assumption that their items elicit information only about the trait they are supposed to measure. However, different response biases may threaten this assumption. Specifically, in children, the response style of acquiescence is an important source of systematic error. Balanced scales, including an equal number of positively and negatively keyed items, have been proposed as a solution to control for acquiescence, but the reasons why this design feature worked from the perspective of modern psychometric models have been underexplored. Three methods for controlling for acquiescence are compared: classical method by partialling out the mean; an item response theory method to measure differential person functioning (DPF); and multidimensional item response theory (MIRT) with random intercept. Comparative analyses are conducted on simulated ratings and on self‐ratings provided by 40, 649 students (aged 11–18) on a fully balanced 30‐item scale assessing conscientious self‐management. Acquiescence bias was explained as DPF and it was demonstrated that: the acquiescence index is highly related to DPF; balanced scales produce scores controlled for DPF; and MIRT factor scores are highly related to scores controlled for DPF and the random intercept is highly related to DPF.